4(2x−1)+4x−4=

−32

1 answer

Let's solve the equation step by step:

Given the equation:

\[ 4(2x - 1) + 4x - 4 = -32 \]

  1. Distribute the \(4\) in the first term:

\[ 8x - 4 + 4x - 4 = -32 \]

  1. Combine like terms on the left side:

\[ (8x + 4x) + (-4 - 4) = -32 \] \[ 12x - 8 = -32 \]

  1. Add \(8\) to both sides to isolate the \(x\) terms:

\[ 12x - 8 + 8 = -32 + 8 \] \[ 12x = -24 \]

  1. Divide both sides by \(12\) to solve for \(x\):

\[ x = \frac{-24}{12} = -2 \]

So, the solution to the equation is:

\[ \boxed{-2} \]